Testing the disk instability model of cataclysmic variables - Dubus, Guillaume; Otulakowska-Hypka, Magdalena; Lasota, Jean-Pierre (Astronomy and astrophysics (Berlin), 2018)
Context. The disk instability model (DIM) attributes the outbursts of dwarf novae to a thermal-viscous instability of their accretion disk, an instability to which nova-like stars are not subject. Aims. We aim to test the fundamental prediction of the DIM: the separation of cataclysmic variables (CVs) into nova-likes and dwarf novae depending on orbital period and mass transfer rate from the companion. Methods. We analyzed the light curves from a sample of ≈130 CVs with a parallax distance in the Gaia DR2 catalog to derive their average mass transfer rate. We validated the method for converting optical magnitude to mass accretion rate against theoretical light curves of dwarf novae. Results. Dwarf novae (resp. nova-likes) are consistently placed in the unstable (resp. stable) region of the orbital period – mass transfer rate plane predicted by the DIM. None of the analyzed systems present a challenge to the model. These results are robust against the possible sources of error and bias that we investigated. Light curves from Kepler or, in the future, the LSST or Plato surveys, could alleviate a major source of uncertainty, that is, the irregular sampling rate of the light curves, assuming good constraints can be set on the orbital parameters of the CVs that they happen to target. Conclusions. The disk instability model remains the solid basis on which to construct an understanding of accretion processes in CVs.